2005
DOI: 10.1097/01.cad.0000176502.40810.b0
|View full text |Cite
|
Sign up to set email alerts
|

Taurolidine–a new drug with anti-tumor and anti-angiogenic effects

Abstract: Taurolidine [bis(1,1-dioxoperhydro-1,2,4-thiadiazinyl-4)-methane (TRD)], a product derived from the aminosulfoacid taurin, was first described as an anti-bacterial substance. It was mainly used in the treatment of patients with peritonis as well as antiendoxic agent in patients with systematic inflammatory response syndrome. Meanwhile, quite interesting new experimental findings elucidated several new mechanisms concerning not only antibiotic but also anti-tumor effects. TRD significantly reduces the pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 38 publications
1
62
0
Order By: Relevance
“…A possible application is discussed in the treatment of tumors since it has been shown that taurolidine promotes apoptosis of tumor cells [12].…”
mentioning
confidence: 99%
“…A possible application is discussed in the treatment of tumors since it has been shown that taurolidine promotes apoptosis of tumor cells [12].…”
mentioning
confidence: 99%
“…11,18) The clinical application of TRD is an antiseptic. It has been used as an intraperitoneal antiseptic for the treatment and prevention of infection in contaminated surgery.…”
Section: Discussionmentioning
confidence: 99%
“…10) Recently, the anti-adherent effect of taurolidine in cancer cells was revealed. 11,12) There have been no reports on TRD pleurodesis. We have been used TRD for pleural space irrigation in patients with empyema and observed regional chest pain and faster air leak cessation after TRD irrigation in postoperative patients.…”
Section: Introductionmentioning
confidence: 99%
“…Taurolidine was well-tolerated, and encouraging initial results were reported in patients with pancreatic and stomach cancer, colo-rectal cancer and tumors of the central nervous system. [10][11][12] Yours sincerely, C. Braumann R. W. Pfirrmann…”
Section: To the Editormentioning
confidence: 99%